Waqf Exchange in Four Mazhabs of Jurisprudence: A Case Study of Infrastructure Projects in Indonesia - Shofiyulloh; Rufaida, Arini; Maulana, Muhammad Dava (International Journal of Social Science and Religion (IJSSR), 2024)
The infrastructure development program planned by the Joko Widodo administration in several regions, especially in Purbalingga and Tegal, displaced several waqf lands. This study analyzes the process of waqf exchange in the project from the perspective of the four madhhabs. This research uses a comparative approach by comparing several opinions of the scholars of the fiqh schools of thought on waqf swaps on the same side and, at the same time, also explaining the different sides. What is interesting in the discussion is the solution offered by replacing the waqf land with other land, even though Waqf has a primary principle in its administration, namely, the principle of Waqf must remain eternal (ta'bid al-asl). The theory of benefit becomes an analytical tool for developing a mindset regarding waqf exchange. This research yields the following conclusions. First, waqf management can change according to the public interest as long as the purpose of the Waqf is still to the expectations of the Waqf. Second, waqf exchange is the best solution when there is no other way, as long as the replacement is at least the previous Waqf.